A Case Report on Staphylococcal Scaled Skin Syndrome - Nedamanuru, Kavya; Dampetla, Sai Jyothi; Gopineni, Divya (Indian Journal of Pharmacy Practice)
Staphylococcal Scalded Skin Syndrome (SSSS) is the medical term used to define a skin condition induced by the exfoliative toxins produced by Staphylococcus aureus. It is also called as Ritter disease, Lyell disease and staphylococcal necrolysis of epidermis. SSSS is most common in children and neonates, and it has been described in adults with renal failure, immunologic deficiency, and other chronic illnesses. The epidermolytic toxin causes loss of cell adhesion in the epidermis causing skin damage.In this article, we present a case of 32 days old male child with dark brown coloured macules all over the body. Based on clinical and paraclinical examinations a diagnosis of Staphylococcal scalded skin syndrome was established which responded favourably to antibiotic treatment, hydro-electrolytic re-equilibration, and adequate local hygiene.
Keywords: Staphylococcal Scalded Skin Syndrome; Neonates; Erythematous lesions; Culture sensitivity test; Antibiotic therapy.